Minimizing Resultant Volume

Calculus Level pending

Let a a , b b , c c , and, d d be real constants. Minimize the volume of the region bounded between y = x 4 + a x 3 + b x 2 + c x + d 1 x 2 4 y = \dfrac {x^4 + ax^3 +bx^2 + cx + d} {\sqrt[4]{1 - x^2}} , x = 1 x= -1 and x = 1 x= 1 , when it is revolved about the x x -axis.

If this volume can be expressed as m n π 2 \dfrac mn \pi^2 , where m m and n n are coprime positive integers, submit your answer as m + n m+n .


The answer is 129.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Rocco Dalto
Nov 14, 2016

The Volume V ( a , b , c , d ) = π 1 1 ( x 4 + a x 3 + b x 2 + c x + d ) 2 1 x 2 d x = {\bf V(a,b,c,d) = \pi * \int_{-1}^{1} \dfrac {(x^4 + ax^3 +bx^2 + cx + d)^2} {\sqrt{1 - x^2}} } \: dx=

π 1 1 ( x 8 + 2 a x 7 + ( a 2 + 2 b ) x 6 + 2 ( a b + c ) x 5 + ( 2 d + 2 a c + b 2 ) x 4 + 2 ( a d + b c ) x 3 + ( 2 b d + c 2 ) x 2 + 2 c d x + d 2 ) 1 x 2 d x = {\bf \pi * \int_{-1}^{1} \dfrac {(x^8 + 2a * x^7 + (a^2 + 2b) * x^6 + 2(ab + c) * x^5 + (2d + 2ac + b^2) * x^4 + 2(ad + bc) * x^3 + (2bd + c^2) * x^2 + 2cd * x + d^2) } {\sqrt{1 - x^2}} } \: dx =

Let x = s i n θ d x = c o s θ d θ {\bf x = sin\theta \implies dx = cos\theta \: d\theta \implies }

V ( a , b , c , d ) = π π 2 π 2 ( ( 1 c o s ( 2 θ ) 2 ) 4 + 2 a ( 1 c o s 2 θ ) 3 s i n θ + ( a 2 + 2 b ) ( 1 c o s ( 2 θ ) 2 ) 3 + {\bf V(a,b,c,d) = \pi * \int_{\frac {-\pi}{2} }^{\frac{\pi}{2}} ((\frac{1 - cos(2\theta)}{2})^4 + 2a(1 - cos^2\theta)^3 sin\theta + (a^2 + 2b) (\frac{1 - cos(2\theta)}{2})^3 + } 2 ( a b + c ) ( 1 c o s 2 θ ) 2 s i n θ + ( 2 d + 2 a c + b 2 ) ( 1 c o s ( 2 θ ) 2 ) 2 + 2 ( a d + b c ) ( 1 c o s 2 θ ) s i n θ + {\bf 2(ab + c) (1 - cos^2\theta)^2 sin\theta + (2d + 2ac + b^2) (\frac{1 - cos(2\theta)}{2})^2 + 2(ad + bc) (1 - cos^2\theta) sin\theta + } ( 2 b d + c 2 ) ( 1 c o s ( 2 θ ) 2 ) + {\bf (2bd + c^2) (\frac{1 - cos(2\theta)}{2}) + } 2 c d s i n θ + d 2 ) d θ . {\bf 2cd sin\theta + d^2) \: d\theta. }

After simplifying we obtain:

I 1 = π 16 π 2 π 2 ( 1 c o s ( 2 θ ) 2 ) 4 d θ = 35 128 π 2 {\bf I_{1} = \frac{\pi}{16} * \int_{\frac {-\pi}{2} }^{\frac{\pi}{2}} (\frac{1 - cos(2\theta)}{2})^4 \: d\theta = \frac{35}{128} \pi^2 }

I 2 = 2 a π π 2 π 2 ( 1 c o s 2 θ ) 3 s i n θ d θ = 0 {\bf I_{2} = 2a \pi * \int_{\frac {-\pi}{2} }^{\frac{\pi}{2}} (1 - cos^2\theta)^3 sin\theta \: d\theta = 0}

I 3 = ( a 2 + 2 b 8 ) π π 2 π 2 ( 1 c o s ( 2 θ ) ) 3 d θ = 5 16 ( a 2 + 2 b ) π 2 {\bf I_{3} = (\frac{a^2 + 2b}{8}) \pi * \int_{\frac {-\pi}{2} }^{\frac{\pi}{2}} (1 - cos(2\theta))^3 \: d\theta = \frac{5}{16} (a^2 + 2b) \pi^2 }

I 4 = 2 ( a b + c ) π π 2 π 2 ( 1 c o s 2 θ ) 2 s i n θ d θ = 0 {\bf I_{4} = 2(ab + c) \pi * \int_{\frac {-\pi}{2} }^{\frac{\pi}{2}} (1 - cos^2\theta)^2 sin\theta \: d\theta = 0 }

I 5 = ( 2 d + 2 a c + b 2 4 ) π π 2 π 2 ( 1 c o s ( 2 θ ) ) 2 d θ = 3 8 ( b 2 + 2 a c + 2 d ) π 2 {\bf I_{5} = (\frac{2d + 2ac + b^2}{4}) \pi * \int_{\frac {-\pi}{2} }^{\frac{\pi}{2}} (1 - cos(2\theta))^2 \: d\theta = \frac{3}{8} (b^2 + 2ac + 2d) \pi^2 }

I 6 = 2 ( a d + b c ) π π 2 π 2 ( 1 c o s 2 θ ) s i n θ d θ = 0 {\bf I_{6} = 2(ad + bc) \pi * \int_{\frac {-\pi}{2} }^{\frac{\pi}{2}} (1 - cos^2\theta) sin\theta \: d\theta = 0 } , I 6 = I 4 = I 2 = 0 {\bf I_{6} = I_{4} = I_{2} = 0 }

I 7 = 2 b d + c 2 2 π π 2 π 2 ( 1 c o s ( 2 θ ) ) d θ = ( 2 b d + c 2 2 ) π 2 {\bf I_{7} = \frac{2bd + c^2}{2} \pi * \int_{\frac {-\pi}{2} }^{\frac{\pi}{2}} (1 - cos(2\theta)) \: d\theta = (\frac{2bd + c^2}{2}) \pi^2 }

I 8 = d 2 π 2 {\bf I_{8} = d^2 \pi^2 }

{\bf \implies }

V ( a , b , c , d ) = π 2 ( 35 128 + 5 16 ( a 2 + 2 b ) + 3 8 ( b 2 + 2 a c + 2 d ) + 1 2 ( 2 b d + c 2 ) + d 2 ) {\bf V(a,b,c,d) = \pi^2 * (\frac{35}{128} +\frac{5}{16}(a^2 + 2b) + \frac{3}{8} (b^2 + 2ac + 2d) + \frac{1}{2} (2bd + c^2) + d^2) }

{\bf \implies }

V a = 0 5 a + 6 c = 0 {\bf \frac{\partial {V}}{\partial {a}} = 0 \implies 5a + 6c = 0 }

V c = 0 3 a + 4 c = 0 {\bf \frac{\partial {V}}{\partial {c}} = 0 \implies 3a + 4c = 0 }

a = c = 0 {\bf \implies a = c = 0 }

V b = 0 6 b + 8 d = 5 {\bf \frac{\partial {V}}{\partial {b}} = 0 \implies 6b + 8d = -5 }

V d = 0 4 b + 8 d = 3 {\bf \frac{\partial {V}}{\partial {d}} = 0 \implies 4b + 8d = -3 }

b = 1 , d = 1 8 {\bf \implies b = -1, d = \frac{1}{8} }

and, 2 V a 2 = 5 8 π 2 > 0 {\bf \frac{\partial^2V}{\partial a^2} = \frac{5}{8} \pi^2 > 0 }

2 V b 2 = 3 4 π 2 > 0 {\bf \frac{\partial^2V}{\partial b^2} = \frac{3}{4} \pi^2 > 0 }

2 V c 2 = π 2 > 0 {\bf \frac{\partial^2V}{\partial c^2} = \pi^2 > 0 }

2 V d 2 = 2 π 2 > 0 {\bf \frac{\partial^2V}{\partial d^2} = 2 \pi^2 > 0 }

and, the Hessian matrix

M = π 2 [ 5 8 0 0 0 0 3 4 0 0 0 0 1 0 0 0 0 2 ] {\bf M = \pi^2 * [ \begin{array}{cccc} \frac{5}{8} & 0 & 0 & 0 \\ 0 & \frac{3}{4} & 0 & 0 \\ 0 & 0 & 1 & 0 \\ 0 & 0 & 0 & 2 \\ \end{array} ] }

d e t ( M ) > 0 {\bf det(M) > 0 \implies }

we have a minimum value at ( 0 , 1 , 0 , 1 8 ) {\bf (0, -1, 0, \frac{1}{8}) }

V = 1 128 π 2 = m n π 2 {\bf \implies V = \dfrac{1}{128} \pi^2 = \dfrac mn \pi^2 \implies }

m + n = 129. {\bf m + n = 129. }

Haha, this is the exact same question as @Guillermo Templado 's problem !

Pi Han Goh - 4 years, 7 months ago

Log in to reply

I'm going to continue with my problem, the next two propositions are impressive... Hold on , they're coming...

Guillermo Templado - 4 years, 7 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...